Serological surveillance of influenza in an English sentinel network: pilot study protocol - De Lusignan, S; Borrow, R; Tripathy, M; Linley, E; Zambon, M; Hoschler, K; Ferreira, F; Andrews, N; Yonova, I; Hriskova, M; Rafi, I; Pebody, R (BMJ Journals, 2019)
BACKGROUND: Rapidly undertaken age-stratified serology studies can produce valuable data about a new emerging infection including background population immunity and seroincidence during an influenza pandemic. Traditionally seroepidemiology studies have used surplus laboratory sera with little or no clinical information or have been expensive detailed population based studies. We propose collecting population based sera from the Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC), a sentinel network with extensive clinical data. AIM:To pilot a mechanism to undertake population based surveys that collect serological specimens and associated patient data to measure seropositivity and seroincidence due to seasonal influenza, and create a population based serology bank. METHODS AND ANALYSIS: Setting and Participants: We will recruit 6 RCGP RSC practices already taking nasopharyngeal virology swabs. Patients who attend a scheduled blood test will be consented to donate additional blood samples. Approximately 100-150 blood samples will be collected from each of the following age bands - 18- 29, 30- 39, 40- 49, 50- 59, 60- 69 and 70+ years. METHODS: We will send the samples to the Public Health England (PHE) Seroepidemiology Unit for processing and storage. These samples will be tested for influenza antibodies, using haemagglutination inhibition assays. Serology results will be pseudonymised, sent to the RCGP RSC and combined using existing processes at the RCGP RSC secure hub. The influenza seroprevalence results from the RCGP cohort will be compared against those from the annual PHE influenza residual serosurvey. ETHICS AND DISSEMINATION: Ethical approval was granted by the Proportionate Review Sub- Committee of the London - Camden & Kings Cross on 6 February 2018. This study received approval from Health Research Authority on 7 February 2018. On completion the results will be made available via peer-reviewed journals.